Accounting rules resources impact on Jordan Islamic bank - Abdullah Ibrahim Nazal; Fuad Al-Fasfus (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2018)
Purpose: Jordan Islamic bank faces choices to apply accounting data in its statements. There is need to explain the choice impact based on its resource in order to promoting its results to customers and sharers. This paper aims to propose exploring deference between Shari'ha accounting rule, government accounting rule, and IFRS, also shows the deference impacts on Jordan Islamic bank accounting data as practically case to promoting its results Design/methodology/approach: Comparing between Shari'ah accounting data resource and law accounting resource practically by analysis Jordan Islamic bank (SSB) report and external auditor report, also analysis its financial statements accounting rules from 2010 -2016 in order to find managing choice of accounting data Findings: Jordan Islamic bank managing has choice to apply assets by market price as fixed standard in order to meet Law and Shari'ha. When it used other law choices, it will get some advantages as use asset value based on depreciation to reduce tax, and use choice of historical price to avoid reducing of assets value by market pricing in future, also policies of accounting profit and distributing are impacted by manager choice to meet the bank continuous than common shareholders returns and customers returns. Originality/value: - It explained problem of Islamic banks accounting based on deference of accounting data resources and showed the Figh Shai'ha accounting rules to meet the real needs of disclosure in Islamic banks.
Keywords: 330; Shari'ha; financial report; accounting; control; international account